On approximations of the de Rham complex and their cohomology. Issue 4 (3rd April 2018) - Bavula, V. V.; Akcin, H. Melis Tekin
ABSTRACT: For a commutative algebra R, its de Rham cohomology is an important invariant of R . In the paper, an infinite chain of de Rham-like complexes is introduced where the first member of the chain is the de Rham complex. The complexes are called approximations of the de Rham complex . Their cohomologies are found for polynomial rings and algebras of power series over a field of characteristic zero.